Pengaruh Karakteristik Chief Executive Officer (CEO) terhadap Kinerja Perusahaan - Jao, Robert; Holly, Anthony; Mardiana, Ana; Oktavianus, Mario (Jurnal Widya Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of Chief Executive Officer (CEO) characteristics on firm performance. This study uses an upper-echelon theory. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. A total of 290 samples were generated using the purposive sampling method in this study. This study found that CEO gender, narcissism, education, and tenure had a positive and significant effect on firm performance. However, CEO power had a negative and insignificant effect on firm performance.